Impact of aortopulmonary collateral flow and single ventricle morphology on longitudinal hemodynamics in Fontan patients: A serial CMR study. (15th July 2020) - Latus, Heiner; Kruppa, Pia; Hofmann, Lucas; Reich, Bettina; Jux, Christian; Apitz, Christian; Schranz, Dietmar; Voges, Inga; Khalil, Markus; Gummel, Kerstin
Abstract: Background: Single ventricle (SV) patients with a Fontan circulation are at risk for functional deterioration. The aim of this study was to assess longitudinal Fontan hemodynamics using serial cardiovascular magnetic resonance (CMR) data and to study the impact of aortopulmonary collateral (APC) flow and type of SV morphology. Methods: Forty-one Fontan patients (age at first CMR 13.4 ± 6.0 years) with two CMR examinations within a time interval of at least 4 years (follow-up 5.3 ± 0.9 years) were included. The protocol consisted of short-axis cine volumetry and 2-dimensional blood flow measurements in the inferior vena cava (IVC), superior vena cava (SVC) and ascending aorta (Ao). APC flow was calculated as Ao – (SVC + IVC). Myocardial strain/strain rate was assessed using feature tracking technique. Results: SV end-diastolic volume (p = 0.14) and ejection fraction (p = 0.70) remained constant. No significant changes in CMR derived myocardial strain/strain rate values were observed. Ao flow decreased (p = 0.01), IVC flow remained unchanged (p = 0.52), while SVC flow (p = 0.003) and APC flow (p = 0.006) decreased significantly. Patients with a systemic right ventricle (RV) showed unchanged APC flow and a further increase in SV size over time compared to patients with a systemic left ventricle. Conclusions: Longitudinal CMR data in a cohort of clinically stable Fontan patients revealed no significant changes in SV dimensions and myocardial performance while APC flow decreased spontaneously. Patients with a systemic RV seem to be at risk for permanent SV volume overload through APCs and might therefore benefit from consequent interventional APC embolization. Highlights: In a clinically stable Fontan cohort SV size and function remained unchanged after 4-year follow-up. APC flow decreased spontaneously in the entire study population. The group with a systemic RV showed unchanged APC flow and progressive SV dilatation. Systemic RV patients may therefore benefit from consequent interventional APC embolization.